Compression stockings used during two soccer matches improve perceived muscle soreness and high-intensity performance - Gimenes, S. V.; Marocolo, M.; Pavin, L. N.; Spigolon, L. M. P.; Neto, O. B.; da Silva, B. V. C.; Duffield, R.; da Mota, G. R. (The Journal of Strength and Conditioning Research, 2021)
Evidence on the use of compression stockings (CS) during soccer matches is limited. Thus, we evaluated the acute effects of CS on match-based physical performance indicators and perceptual responses during 2 consecutive soccer matches with 72-hour recovery. Twenty outfield players were randomly allocated to the CS group (20-30 mm Hg) or control group (non-CS) and performed 2 matches (5 players using CS or regular socks per team/match). Match loads {rating of perceived exertion × minutes; CS ~830 vs. control 843 (arbitrary units [AU])} and heart rate (HR) responses (both CS and control ~86% HRpeak) did not differ (p > 0.05) between CS and control groups. Although total distance covered did not differ (p > 0.05) between groups, CS increased distances (effect size [ES] = 0.9-1.32) in higher-speed zones (>19 km/h CS ~550 m vs. control ~373 m) alongside an increased number of accelerations (-50.0 to -3.0 m/s²) than control (CS: 33.7 ± 11.2 vs. control: 23.8 ± 7.9; p = 0.003; ES = 1.04). Perceived recovery did not differ (p > 0.05) between groups for either match but was worse in the second match for both groups. Perceived muscle soreness increased in control after match 2 (from 3.1 ± 1.9 to 6.3 ± 1.6 AU; p < 0.0010) but did not in CS (from 2.8 ± 1.4 to 4.1 ± 1.9 AU; p = 0.6275; ES = 1.24 CS vs. control after match). Accordingly, CS use during 2 soccer matches with 72-hour recovery reduces perceived muscle soreness in the second match and increases higher-speed match running performance.